2019
DOI: 10.1021/acsabm.9b00769
|View full text |Cite
|
Sign up to set email alerts
|

Reduction-Responsive Polymer Prodrug Micelles with Enhanced Endosomal Escape Capability for Efficient Intracellular Translocation and Drug Release

Abstract: High-efficiency endosomal escape of drug delivery nanocarriers for glutathione-based reduction-responsive drug release in cytoplasm can significantly enhance the therapeutic efficacy of the loaded therapeutic drugs. In this report, we develop the polymer prodrug micelles self-assembled from the amphiphilic block copolymer prodrug, PEG-b-P­(CPTM-co-ImOAMA), consisting of poly­(ethylene glycol) (PEG) and copolymerized segments of disulfide bond-linked camptothecin methacrylate monomer (CPTM) and 1-(1H-imidazole-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
(75 reference statements)
0
16
0
Order By: Relevance
“…This may be attributed to the synergistic effects of multiple therapeutic agents [113,114]. Remarkably, to assess the general biosafety of drug conjugates, Ibrahim et al have gone further into in vivo investigation of the drug conjugates developed by their group [115]. The organs of mice exposed to these drug conjugates for 21 days were sliced and analyzed histologically.…”
Section: Mechanism Of Cleavage Methods Of Hydrolysis Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be attributed to the synergistic effects of multiple therapeutic agents [113,114]. Remarkably, to assess the general biosafety of drug conjugates, Ibrahim et al have gone further into in vivo investigation of the drug conjugates developed by their group [115]. The organs of mice exposed to these drug conjugates for 21 days were sliced and analyzed histologically.…”
Section: Mechanism Of Cleavage Methods Of Hydrolysis Referencesmentioning
confidence: 99%
“…Similarly, more recent studies have further shown that covalent linked prodrugs improve the pharmacokinetics and biodistribution of the conjugated drug as reported by Ibrahim and co-workers. H22 tumor model was induced in BALB/c [115]; the mice were exposed to conjugated drug delivery system and free-drug camptothecin (CPT), respectively. From the results, conjugates had a significantly had better pharmacokinetic profile than the free drug, this also led to increased accumulation of the drug within the tumor tissues and consequently better activity.…”
Section: Effect Of Covalent Drugs Conjugation On the Pharmacokinetic mentioning
confidence: 99%
“…The multiple endogenous sensitive smart materials were common in many works, such as dual responsive materials to pH and GSH, 273–277 pH and hypoxia, 131 pH and enzyme, 173 ROS and GSH, 60,278,279 GSH and hypoxia, 280,281 as well as GSH and enzyme 183 . There were also examples of triple responsive materials which were sensitive to pH, GSH, and enzyme 161,282 …”
Section: Multiple‐triggered Smart Materialsmentioning
confidence: 99%
“…The size from TEM analysis observed smaller than the DLS measurements which could be due to difference in the dried state and hydrated state of the nanomicelles. 47,50 Fig. 3c and d, illustrates the SAED patterns of the NM-1 and NM-2.…”
Section: Characterizations Of Nanomicellesmentioning
confidence: 99%